2015
DOI: 10.12973/unibulletin.412.3
|View full text |Cite
|
Sign up to set email alerts
|

Second Language Acquisition of Syntactic Movement in English by Turkish Adult Learners

Abstract: There has been much discussion on the involvement of Universal Grammar (UG) in Second Language Acquisition (SLA) process. Despite growing research in the field, few precise answers to the problem have been suggested so far. Hence, recent L2 studies within the generative framework have shifted from investigating this issue to determining whether or not interlanguage grammars exhibit natural language characteristics (Can, Kilimci & Altunkol, 2007). The present study aimed to investigate L2 acquisition of syntact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…There is some evidence of transfer in the acquisition of polarity items from the small body of previous non-native/bilingual language acquisition research in this area: Austin et al (2013), Agçam (2008), Can and Agçam (2011) and Gil et al (2011). 7 First, Austin et al (2013) investigated whether attrition occurs in the Spanish of Spanish–English bilingual 5–6-year-old children growing up in the USA.…”
Section: Transfer In the Non-native Acquisition Of Polarity Itemsmentioning
confidence: 97%
See 1 more Smart Citation
“…There is some evidence of transfer in the acquisition of polarity items from the small body of previous non-native/bilingual language acquisition research in this area: Austin et al (2013), Agçam (2008), Can and Agçam (2011) and Gil et al (2011). 7 First, Austin et al (2013) investigated whether attrition occurs in the Spanish of Spanish–English bilingual 5–6-year-old children growing up in the USA.…”
Section: Transfer In the Non-native Acquisition Of Polarity Itemsmentioning
confidence: 97%
“…Finally, Agçam (2008) and Can and Agçam (2011) report on an investigation of L2 acquisition of any by adult Turkish-speaking learners of English. They elicited any using a task in which participants completed a partial sentence such as (28a).…”
Section: Transfer In the Non-native Acquisition Of Polarity Itemsmentioning
confidence: 99%
“…Mede et al (2014), who investigated CLI issues with the acquisition of word order in terms of verb placement, found syntax to be a particular challenge. Agcam et al (2015), focusing on the learning of syntactic movement, found that learners face more problems when noun clauses do not include auxiliary verbs, and also when the movement is in the subject position as opposed to the object position. As can be seen, there is a degree of variance in the results of these studies into Turkish-to-English challenges.…”
Section: Interlingual Interference and Turkish Learners Of Englishmentioning
confidence: 99%
“…However, the study did not return a similar result in the productive task which involved describing a picture (Balabakgil et al, 2015). Agcam et al (2015) also incorporated three task types into their study on the learning of syntactic movement by Turkish learners of English: a grammaticality judgment task, a scrambled sentence task, and an elicited imitation task. The results again suggested that task type variation affects findings significantly, with participants achieving higher accuracy rates in the grammaticality judgment test (Agcam et al, 2015).…”
Section: Interlingual Interference and Turkish Learners Of Englishmentioning
confidence: 99%
See 1 more Smart Citation